KESALAHAN SISWA DALAM MENYELESAIKAN SOAL SPLDV - Rahayu S, Putri (JISPE Journal of Islamic Primary Education, 2021)
The SPLDV material which many student considered difficult si that many made mistake in solving the material problem led the researcher to carry out further analysis. Based on this, the purpose of this paper is to describe the student’ mistake in solving SPLDV questions. This study is a descriptive research with qualitative approach. Subjects in this study were students of VIII class in SMP Negeri 1 Salam, Magelang District, with 32 students. data collection was performed by using test and non test instruments. The results of this study show that most students still make a mistake in solving the SPLDV problem. The analysis is done by using the Newman stages. From the results of the study found that at the reading stage students experience errors in reading commands written in the question. In the comprehension stage students can create equations using variables, but does not explain the purpose of the variables used in addition to the students are also wrong in interpreting the intent of the given problem. At the transformation stage students difficulty in the transform contextual problem to the mathematical sentence. At the process skill stage students make error in algebra operations that result in miscalculation so that student answers are wrong. At the encoding stage the student has an error in converting the result into a constextual sentence or making a conclusion.